Culture and Educational Policy in Uganda - Gyagenda, AbdulSwamad (Interdisciplinary Journal of Education, 2024)
Cultural beliefs have a significant influence on the values of a society. Policy makers cannot ignore culture while planning for educational reforms. In a country like Uganda that is multi-cultured, the task of addressing all cultural needs becomes a little tricky. In this paper the author has tried to analyse the body of existing literature on the subject and been able to identify some cultural issues affecting educational policy such as misconceptions, cultural conservatism, multi-culturalism, early-marriages, multiple languages, gender parity among others. Various conclusions and recommendations are made and they include but not limited to; affirmative action, intercultural dialogue, decentralisation of educational policies, promotion of globalisation and human rights.